Growth and Yield of Six Soybean Genotypes on Short-term Flooding Condition in the Type-B Overflow Tidal Swamps - Sagala, Danner; Ghulamahdi, Munif; Trikoesoemaningtyas, Trikoesoemaningtyas; Lubis, Iskandar; Shiraiwa, Tatsuhiko; Homma,; Koki (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
A study to explore the agronomic response of some soybean genotypes to temporary flooding in the type-B overflow tidal swamp and to obtain the adaptive genotype to the environment was arranged in a split-plot design at coordinates 2°64’46.77” S and 104°75’27.75” E with an altitude of 3.5 m above sea level. The main plot was subject to short-term flooding with a variety of cultivation technologies consisting of saturated soil culture (SSC) for one month without flooding, SSC for one month with flooding, SSC during plant growth without flooding, SSC during plant growth with flooding and non-SSC/dry cultivation. The subplot was soybean genotype consisting of 6 genotypes: Tanggamus, Karasumame (Naihou), M652, Anjasmoro, M100-47-52-13, and Tachinagaha. The result showed that impaired soybean growth at the beginning of the growth stage caused pressure on the later growth stage and decreased soybean yield. Short-term flooding reduced the soybean yield. The non-tropical genotypes of Karasumamae (Naihou), M652 and Tachinagaha produced the lowest yield of seeds; 20% lower than the tropical genotypes of Anjasmoro, M100-47-52-13 and Tanggamus with SSC during plant growth without flooding treatment. The Karasumame (Naihou) genotype produced the highest seed yield of the three non-tropical genotypes. Anjasmoro and M100-47-52-13 produced the highest seed yield at temporary flooding.